Socio-technical issues in diversifying rice-based irrigation systems - Moya, T. B.; Miranda, S.M. (1989)
Since the early 60s many rice-producing countries in Asia have launched agricultural diversification projects to stimulate farm productivity. However, these projects have succeeded in only a few countries. Perhaps, the pressure to diversify agriculture, especially the irrigated rice systems, were less compelling then than today.